Analysis Of Economy Ratio And Growth Ratio In Report Of Budget Realization Of The Regional Development Planning Agency (Bappeda) In Building Medan City Due To Covid-19 - Murni Sofiah; Wahyu Syarvina (Penerbit Jurnal Indonesia, 2022)
Development is a planned process aimed at improving people's welfare. One of the most important processes is development planning, which requires an annual budget to realize the planned program. The purpose of this study was to determine the effect of economic ratios and growth ratios on the realization of the Bappeda budget in developing Medan City during the Covid-19 period. This research was conducted at the Medan City Regional Development Planning Agency. The method used in this research is descriptive quantitative method. The data collection method used is observation and documentation by taking secondary data. The analytical technique used is using the Economy Ratio and Growth Ratio measurement methods. The results of this study say that Covid is indicated in Indonesia in 2020, so in 2019 there is no such indication, in the 2019-2021 Bappeda Budget Realization Report there are differences in the budget and realization each year. In 2019 the budget was 10,943,903,735 and the realization was 6,068,358,002. In 2020 the budget is 10,419,108,595 and the realization is 5,531,644,863. In 2021 the budget is 24,292,278,919 and the realization is 16,315,636,163. In 2021 Budget and Realization will increase by 2.21% and 2.68% from 2019. 595 and Realization of 5,531,644,863. In 2021 the budget is 24,292,278,919 and the realization is 16,315,636,163. In 2021 Budget and Realization will increase by 2.21% and 2.68% from 2019. 595 and Realization of 5,531,644,863. In 2021 the budget is 24,292,278,919 and the realization is 16,315,636,163. In 2021 Budget and Realization will increase by 2.21% and 2.68% from 2019.